2022
DOI: 10.1177/02673231211072669
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ digital competence in guiding and supervising young children's use of the Internet

Abstract: Children use the Internet at an increasingly younger age and many parents do not have the necessary knowledge to protect or guide them. A previous study showed that 78% of children between the ages of 6 and 9 used the Internet and that their parents were usually with them, but 40% of these children would surf at some point without supervision. This research aims to examine the relationship between the parents' digital competence and the different elements included in the parental mediation process. The sample … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…With immediate access to global information, children and adolescents are expanding their worldviews and learning styles, as well as extending social networks across distance and culture. Another result found that some parents consider the educational value of applications to be important during the selection of content and applications appropriate to their children (Pons-Salvador et al, 2022). Thus, it allows parents to further encourage their children to use smartphones for useful purposes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With immediate access to global information, children and adolescents are expanding their worldviews and learning styles, as well as extending social networks across distance and culture. Another result found that some parents consider the educational value of applications to be important during the selection of content and applications appropriate to their children (Pons-Salvador et al, 2022). Thus, it allows parents to further encourage their children to use smartphones for useful purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Parents' digital competence was measured using Digital Competence Instrument (Pons-Salvador et al, 2022). It includes eight items related to activities that parents might be able to do, with items (1) blocking messages from someone you do not want to contact, (2) finding information on how to use the Internet safely, (3) putting a page on a bookmark, (4) changing privacy profile settings on a social media, (5) comparing different websites to contrast information, (6) deleting the history of pages visited, (7) blocking unwanted advertisements or "spam," and (8) change filter preferences in an online shop.…”
Section: Instrumentsmentioning
confidence: 99%
“…The digital competence of the parents also translated into the early acquisition of digital skills by the children (Saçkes et al, 2011). Parents proficient in digital tools were more likely to urge their children to use Microsoft PowerPoint and the Internet to produce learning materials (Tran et al, 2020), even among children as young as six years (Pons-Salvador et al, 2022).…”
Section: Parental Mediation Of Digital Device Use By Childrenmentioning
confidence: 99%
“…Under supervision, parents kept time limits for the usage of digital devices. Pons-Salvador et al (2022) observed that parents of children aged 6-9 years would allow children to go online with maximum supervision and are themselves digitally competent and are aware of activities children do online. However, the participants of this study exhibited a supervision mediation preference even https://doi.org/10.21428/8c225f6e.e3307987 when they were not digitally competent enough in most cases, and exercised the mediation of children even beyond the age of 9 years.…”
Section: Parental Mediation Strategiesmentioning
confidence: 99%
“…Researchers, teachers, next of kin, and government agencies are concerned about the potentially harmful influences of social media; these concerns relate to the ongoing increases in the time that adolescents spend in front of screens (Elhai et al 2021), the negative and even dangerous communications they may encounter online (Hjetland et al 2021), as well as the perceived vulnerability of young people (Valkenburg et al 2022). According to Pons-Salvador et al (2022), most parents are aware of the benefits and risks of the Internet, but many of them did not know what to do to protect their children. More than half of the parents said they did not know how to set up content filters or manage parental control, and 40% did not know how to block unwanted advertisements.…”
Section: Literature Reviewmentioning
confidence: 99%